TRANSLATION AND THE TEACHING OF LINGUISTICS IN KISWAHILI IN KENYAN UNIVERSITIES - Odhiambo, Owala Silas (International Journal of Research -GRANTHAALAYAH, 2022)
This article explores community relations in military operations in Nigeria. Initially, it notes that the interaction between the military and the civilian population is inevitable both in times of peace and during conflicts, while occasionally this interaction even requires and/or results in the use of force or arms for the achievement of the goals of the operations. Consequently, human rights are violated in the process. This article thus seeks to assess the derogation and limitation of human rights on the premise of national security, public safety and order as the arguments for the justification for violations of the rights during military operations and argues that a balance must be found between derogation and limitation of the rights on the one hand and the respect for and protection of the enjoyment of the right and freedoms on the other hand. The article thus recommends the integration of human rights into military law and training of commissioned and non-commissioned officers in the Nigeria Military.